Pendampingan Penerapan Kurikulum OBE dan Persiapan Akreditasi LAM Teknik Bagi Perguruan Tinggi Teknik (Fakultas Teknik, Universitas Brawijaya, 2025)
Universities in Indonesia continue to improve the quality of education, including in terms of curriculum and accreditation in accordance with regulations issued by the Ministry of Education, Culture, Research and Technology (KEMENDIKBUDRISTEK). The OBE (Outcomes-Based Education) curriculum and Engineering Self-Accreditation Agency (LAM) accreditation are two important pillars in achieving this goal. However, a deep understanding of these two pillars is still not comprehensive. Therefore, it is necessary to carry out community service activities in the form of training for lecturers on the OBE Curriculum and Engineering LAM so that they can apply it in the learning process and prepare to obtain Engineering LAM Accreditation. This community service activity will be carried out in 3 Training of Trainer (ToT) series. The first series is about the introduction of accreditation and OBE curriculum. The second series is about the preparation and planning of curriculum implementation and evaluation. The third series is the preparation of LED and LKPS in national accreditation, as well as deeper knowledge about basic science and math and capstone design. This community service activity is expected to achieve several goals, namely increasing lecturers' understanding of the OBE Curriculum and LAM Engineering. In addition, this activity can also improve the ability of lecturers to apply the OBE Curriculum in the learning process and prepare to obtain Engineering LAM Accreditation. In general, this activity can improve the quality of education in order to become a superior university and produce quality graduates.